2019
DOI: 10.3171/2019.6.spine19531
|View full text |Cite
|
Sign up to set email alerts
|

Less invasive spinal deformity surgery: the impact of the learning curve at tertiary spine care centers

Abstract: OBJECTIVEThe past decade has seen major advances in techniques for treating more complex spinal disorders using minimally invasive surgery (MIS). While appealing from the standpoint of patient perioperative outcomes, a major impediment to adoption has been the significant learning curve in utilizing MIS techniques.METHODSData were retrospectively analyzed from a multicenter series of adult spinal deformity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Minimal invasive techniques usually combine posterior percutaneous instrumentation and anterior retroperitoneal approaches using interbody fusion cages. This combined MIS approach has the advantage of sparing paravertebral muscle dissection, minimal blood Experienced surgeons are treating older and more morbid patients with similar outcomes in mild and moderate spinal deformities (14). Sagittal deformity correction mainly relies on powerful interbody reduction methods that imply a resection of the degenerated intervertebral disc and anterior longitudinal ligament.…”
Section: Mismentioning
confidence: 99%
See 1 more Smart Citation
“…Minimal invasive techniques usually combine posterior percutaneous instrumentation and anterior retroperitoneal approaches using interbody fusion cages. This combined MIS approach has the advantage of sparing paravertebral muscle dissection, minimal blood Experienced surgeons are treating older and more morbid patients with similar outcomes in mild and moderate spinal deformities (14). Sagittal deformity correction mainly relies on powerful interbody reduction methods that imply a resection of the degenerated intervertebral disc and anterior longitudinal ligament.…”
Section: Mismentioning
confidence: 99%
“…It has been demonstrated that low back pain and leg pain improve and that the segmental lumbar deformity can be efficiently corrected with MIS techniques. (14,18). This strategy seems appropriate in mild and moderate ASD which present degenerative changes of the lumbar spine and a remaining curve flexibility (19).…”
Section: Mismentioning
confidence: 99%
“… 19 In addition, a longitudinal multicenter analysis of minimally invasive surgery identified a shift toward ALIF surgery and away from three-column osteotomies with the advent of hyperlordotic cages; however, centers continue to differ in their use of lateral ACR and posterior osteotomy techniques. 20 It is evident that there is no singular approach to planning spinal deformity surgery, and various factors related to the patient’s medical stability and surgeon’s technical abilities must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ASR will become the largest spine registry, there are other highly productive databases that further highlight the importance of this growing area of data science. For example, the International Spine Study Group (ISSG) has published primarily on treatment of adult spinal deformity (ASD) over the past decade and have recently begun to examine long-term outcomes in minimally invasive ASD surgery [14]. Surgical innovation and new technology may drive these evolutions in practice initially, but ultimately favorable long-term outcomes lead to broad acceptance within the field, which now is often augmented by analysis of large surgical databases.…”
Section: Evolution Of Clinical Neurosurgical Databasesmentioning
confidence: 99%